2014
DOI: 10.1097/aog.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Abortion and Mental Health

Abstract: Objective To examine whether a first abortion increases risk of mental health disorders compared to a first childbirth, with and without considering prepregnancy mental health and adverse exposures, childhood economic status, miscarriage history, age at first abortion or childbirth, and race or ethnicity. Methods A cohort study compared rates of mental disorders (anxiety, mood, impulse-control, substance use, eating disorders, and suicidal ideation) among 259 women postabortion and 677 women postchildbirth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…This is one of the first studies to examine predictors of pre-abortion psychological health; results were in the expected direction and they were consistent with other research that has examined some of these factors as predictors of post-abortion psychological health in a nationally representative sample of women (Steinberg & Finer, 2011; Steinberg et al, 2014). Future research could verify these findings in other samples of women having abortions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is one of the first studies to examine predictors of pre-abortion psychological health; results were in the expected direction and they were consistent with other research that has examined some of these factors as predictors of post-abortion psychological health in a nationally representative sample of women (Steinberg & Finer, 2011; Steinberg et al, 2014). Future research could verify these findings in other samples of women having abortions.…”
Section: Discussionsupporting
confidence: 88%
“…We focused on pre-abortion psychological health for two main reasons. First, psychological distress before an abortion is higher compared to any time afterwards (Bradshaw & Slade, 2003; Major et al, 2000; Lowenstein et al, 2006) and compared to other samples as described just above (Antony et al, 1998; Lee et al, 2005; Miller et al, 2006; Thomas et al, 2001); and second, pre-abortion psychological health has consistently been shown to be a strong predictor of post-abortion psychological health (Major et al, 2000; Steinberg et al, 2014). Therefore, helping women reduce pre-abortion psychological distress is warranted and to do that, we need to understand what predicts pre-abortion psychological health.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The simple association between abortion and subsequent mental-health disorders—including mood, anxiety, substance-use disorders, and suicidal ideation—appears open to alternative explanations (Steinberg, Becker, & Henderson, 2011; Steinberg & Finer, 2011; Steinberg, McCulloch, & Adler, 2014; Steinberg & Russo, 2008; Taft & Watson, 2008). In models that control for confounding factors—such as prior mental health, prior or current adverse experiences, and sociodemographic factors—the association between abortion and subsequent mental health evaporates for mood and anxiety disorders, and suicidal ideation (Fergusson, Horwood, & Boden, 2013; Steinberg et al, 2011; Steinberg & Finer, 2011; Steinberg et al, 2014; Steinberg & Russo, 2008; Taft & Watson, 2008). Furthermore, strong predictors of post-pregnancy (including post-birth and post-abortion) mental health were prior mental health, and adverse experiences.…”
Section: Psychological Aspects Of Abortionmentioning
confidence: 99%